The efectiveness of module based on Missouri Mathematics Project model to improve students’ mathematical literacy skills - Rodliyah, Siti Ika Faidatur; Wijayanti, Dyana; Basir, Mochamad Abdul; Dewi, Fatimah Candrawati (Indonesian Journal of Education and Pedagogy, 2024)
The ability that students must have in the 21st-century learning era is mathematical literacy. Generally, the selection and use of inappropriate textbooks is a factor in low mathematical literacy. The research aims to determine the effectiveness of using modules based on the Missouri Mathematics Project model in improving students' mathematical literacy. The type of research used is quantitative, using a one-shot case study. The participants of this study were 27 lower secondary students. The results showed that the module based on the Missouri Mathematics Project model could improve mathematical literacy with a classical completeness of 96%. Additionally, it can be interpreted from a one-sided t-test that the module based on the Missouri Mathematics Project (MMP) model is effective in improving students' mathematical literacy. The findings can assist educators in effectively utilising the modules based on the Missouri Mathematics Project model and its integration into their teaching practices.